2016
DOI: 10.1371/journal.pgen.1006153
|View full text |Cite
|
Sign up to set email alerts
|

Aversive Behavior in the Nematode C. elegans Is Modulated by cGMP and a Neuronal Gap Junction Network

Abstract: All animals rely on their ability to sense and respond to their environment to survive. However, the suitability of a behavioral response is context-dependent, and must reflect both an animal’s life history and its present internal state. Based on the integration of these variables, an animal’s needs can be prioritized to optimize survival strategies. Nociceptive sensory systems detect harmful stimuli and allow for the initiation of protective behavioral responses. The polymodal ASH sensory neurons are the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 121 publications
(192 reference statements)
1
32
1
Order By: Relevance
“…These neurons use cGMP-based sensory transduction pathways (36), as do vertebrate photoreceptors, where RD3 is known to be expressed. We used DiI staining (37) to identify two classes of ciliated sensory neuron that are not known to use cGMP signaling in sensory transduction: the ASH and ADL sensory neurons (36,(38)(39)(40)(41). We did not detect expression of rdl-1::gfp in ASH and ADL neurons ( Fig.…”
Section: Resultsmentioning
confidence: 95%
“…These neurons use cGMP-based sensory transduction pathways (36), as do vertebrate photoreceptors, where RD3 is known to be expressed. We used DiI staining (37) to identify two classes of ciliated sensory neuron that are not known to use cGMP signaling in sensory transduction: the ASH and ADL sensory neurons (36,(38)(39)(40)(41). We did not detect expression of rdl-1::gfp in ASH and ADL neurons ( Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The wild-type phenotype of a regulatory allele tax-2(p694), which only affects a subset of the TAX-2 neurons [30], narrows down the cells required for the ascr#3 response to just six pairs-ASGs, ASIs, ASJs, ASKs, AWBs, and AWCs ( Figure 4B). Using strains in which pairs of specific neurons were genetically ablated [13,[31][32][33], we found that the functions of the ASJ, AWB, and AWC pairs were each required for ascr#3 to counter the effect of ascr#10 ( Figures 4B and S4). We were surprised to discover that, although the ASIs express tax-2/tax-4 and were thus expected to mediate the A B Figure 4.…”
Section: Cgmp-mediated Signaling In Several Neurons Is Required For Amentioning
confidence: 99%
“…However, it is not known if for is involved in the nociceptive-like escape response. PKG has been shown to regulate nociception in several organisms (36)(37)(38). Here, we use an optogenetic screen to show that activation of a subset of for neurons induces a nociceptive-like escape response.…”
mentioning
confidence: 99%